Biokonsentrasi Faktor Logam Berat Timbal (Pb) Dalam Kandungan Ikan di Daerah Pantai Tegal Katilayu Cilacap, Jawa Tengah - Nurlinda Ayu,; Prasadi, Oto; Fadlilah, Ilma (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Around 143,000 people die every year in developing countries due to exposure to the heavy metal lead (Pb). This, combined with increased heavy metal pollution as a result of increasing industry. Lead can enter the bodies of living creatures through food, drink, air, or through the skin. Fossil fuels, cats, pesticides, soil, toys, car batteries and other sources produce lead. Iron (Fe), Manganese (Mn), Zinc (Zn), Cadmium (Cd), Chromium (Cr), Copper (Cu), Lead (Pb), Nickel (Ni), and Mercury (Hg) are pollutant elements heavy metals originating from industry. These heavy metals can be harmful to human health depending on which part of the body they are most bound to. To determine the bioconcentration factor (BCF) of the heavy metal lead (Pb) in the consumption of fish originating from fishing grounds in Tegal Katilayu Cilacap sea waters. Analysis of lead (Pb) levels in sea water and the bodies of tuna, mackerel and tuna was carried out using the Atomic Absorption Spectrophotometry (AAS) instrument at the Jendral Soedirman University Laboratory. Meanwhile, sea air pH measurements were carried out directly while still at the Tegalkatilayu Cilacap waters. The sea air pH obtained was still neutral, namely 7.43 and was still in the range (6.5 -8.0). Based on the results of heavy metal tests using Atomic Absorption Spectrophotometry (AAS) of Tegalkatilayu sea air, a concentration of 0.236 ppm was obtained, which has passed the maximum quality standard of 0.05 ppm. Meanwhile, test results for the heavy metal lead (Pb) in the body of tuna were 2,291 ppm, tuna 2,892 ppm, and mackerel 0,716 ppm. The degree of acidity (pH) in Tegalkatilayu waters is still within the range (6.5 – 8.0), namely an average pH of 7.34. The lead (Pb) content in sea water was found to be an average of 0.236 ppm, according to the Decree of the Minister of Environment of the Republic of Indonesia No. 51 of 2004 concerning sea water quality standards for port waters has exceeded the maximum limit of 0.05 ppm. Meanwhile, the lead (Pb) content in the body of tuna is 2.291 ppm, tuna is 2.892 ppm, and mackerel is 0.716 ppm. This has resulted in marine air pollution and accumulation of the heavy metal lead (Pb) in fish bodies. The bioconcentration of heavy metal factors contained in the fish's body was found to be <100, which is still in the low category. There needs to be regular monitoring regarding the maximum fish consumption limit for humans per week which has accumulated heavy metals based on body weight, age and gender. Thus, it can reduce the accumulation of the heavy metal lead (Pb) in the human body. Keywords: pH of sea water, bioconcentration of heavy metal factors.